2020
DOI: 10.1108/ijmhsc-04-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, mental health and urban migrants: a narrative review

Abstract: Purpose The purpose of this paper is to provide a narrative review of the literature on mental health resilience and other positive mental health capacities of urban and internal migrants. Design/methodology/approach The methodology for this narrative review included a search of articles published up to 2017. The abstracts were screened and relevant articles studied and discussed. Literature on the particular mental health challenges of urban migrants in India was also studied. References found in the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…This finding corroborates the results from other studies. Coope et al found resilience to be protective of mental health in their review among internal migrants in low and middle income countries and this was also seen by Wu et al in their review among both cross border and internal migrant youth across several countries [ 52 , 108 ]). Our findings of the protective nature of resilience contribute to the literature on the role that resilience might play in the promotion of mental health.…”
Section: Discussionmentioning
confidence: 56%
“…This finding corroborates the results from other studies. Coope et al found resilience to be protective of mental health in their review among internal migrants in low and middle income countries and this was also seen by Wu et al in their review among both cross border and internal migrant youth across several countries [ 52 , 108 ]). Our findings of the protective nature of resilience contribute to the literature on the role that resilience might play in the promotion of mental health.…”
Section: Discussionmentioning
confidence: 56%
“…Factors which may confer resilience to adverse mental health outcomes in migrants also warrants investigation. 42 …”
Section: Discussionmentioning
confidence: 99%
“…In mental health scholarship, the idea of resilience was pioneered within developmental psychology and studies of stress-resistant children (Garmezy, 1974). Definitions of resilience in healthcare vary, but they usually include three key features: (a) identification of risks or adversity, (b) identification of sources or resources to help offset the effects of that adversity, (c) avoiding the effects of the adversity or adapting positively to it (Coope et al, 2020; Seaman et al, 2014, p. 3).…”
Section: Resilience In Cross Cultural Contextmentioning
confidence: 99%
“…While the potential problems of migration and their possible mental health sequelae are widely discussed there have so far been relatively few empirical studies of resilience and internal migration in low-to-middle-income countries. Coope et al (2020) provide a review of the substantive pieces of work to date and discovered through an extensive literature search only 11 pieces of work on the subject, mainly originating from China but with other countries such as India, Sri Lanka and Ghana represented. All of these pieces of work highlight the value of resilience, say it merits further attention, and identify factors including familial and community networks and individual hope or optimism.…”
Section: Resilience In Cross Cultural Contextmentioning
confidence: 99%